The factors influencing blockchain adoption in hospitals: a pilot study - Bazel, Mahmood A; Ahmad, Mazida; Mohammed, Fathey; Al-Kumaim, Nabil Hasan; Mater, Wasef; Yasin, Azman (2024)
Blockchain technology has gained popularity as a secure and efficient data storage and sharing method, with potential benefits for patient data management, cost reduction, and data security in the healthcare sector. However, the adoption rate of blockchain in healthcare organizations is significantly low. This pilot study aims to verify the validity and reliability of the instrument developed to determine the factors that may be impacting the adoption of blockchain technology by Malaysian hospitals. A small sample of decision-makers in Malaysian hospitals was targeted to collect the preliminary data using an online survey instrument developed based on the Technology-Organizational-Environment (TOE) framework and related studies constructs’ items. The data was analyzed using Partial least squares structural equation modeling (PLS-SEM). The findings confirmed the reliability and validity of the measurement scales. This study contributes to ongoing research on BCT adoption in healthcare organizations and offers insights that can be useful to practitioners and researchers in this field.